Influencing fatty acid composition of yeasts by lanthanides - Kolouchova, Irena; Sigler, Karel; Zimola, Michal; Rezanka, Tomas; Matatkova, Olga; Masak, Jan (World journal of microbiology & biotechnology, 2016)
The growth of microorganisms is affected by cultivation conditions, concentration of carbon and nitrogen sources and the presence of trace elements. One of the new possibilities of influencing the production of cell mass or lipids is the use of lanthanides. Lanthanides are biologically non-essential elements with wide applications in technology and industry and their concentration as environmental contaminants is therefore increasing. Although non-essential, lanthanides have been proposed (and even used) to produce beneficial effects in plants but their mechanisms of action are unclear. Recently, it was suggested that they may replace essential elements or operate as potent blockers of Ca(2+) channels. We tested the effect of low concentrations of lanthanides on traditional biotechnologically useful yeast species (Kluyveromyces polysporus, Saccharomyces cerevisiae, Torulospora delbrueckii), and species capable of high accumulation of lipids (Rhodotorula glutinis, Trichosporon cutaneum, Candida sp., Yarrowia lipolytica). Low concentrations of lanthanum and monazite were conducive to an increase in cell mass and lipids and also higher production of palmitoleic acid, commonly used in cosmetics and medicine, and ω6-linoleic acid which is a precursor of thromboxanes, prostaglandins and leucotrienes.
Keywords: Yeasts; metabolismus lipidů; Fatty acids; Non-oleaginous yeasts; Lipid Metabolism; průmyslová mikrobiologie; Microbial lipids; Lanthanoid Series Elements; Culture Media; biomasa; kvasinky; kultivační média; mastné kyseliny; lanthanoidy; Oleaginous yeasts; Biomass; Industrial Microbiology; Lanthanides; Fatty Acids